Euro area periphery countries' fiscal policy and monetary policy surprises - Oliver Hülsewig; Horst Rottmann (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2021)
In this study, we explore how fiscal policy in euro area periphery countries responds to monetary policy surprises that lower sovereign bond yields. In particular, we assess whether the disciplining effect of financial markets on public finances is undermined by the ability of monetary policy to affect the conditions of external funds. Using Jordà's (2005) local projection method we find that fiscal discipline, on average, does not wane in response to monetary policy innovations that bring down yields on sovereign bonds. The reaction of economic activity to shocks to monetary policy appears to determine the fiscal stance, rather than the adjustment of borrowing cost.
Keywords: E52; E62; H62; 330; Euro area periphery countries; fiscal policy; market discipline; monetary policy shocks; local projections